Desenvolvimento de nanocompósitos poliamida 11 / dióxido de titânio para aplicação na indústria petrolífera - Balarim, Caio Vinicius Morisco (2015)
The depth at which explores offshore oil grew abruptly, forcing the advancement of technology in relation to the knowledge acquired so far. For the risers operating conditions, subject to internal relatively low pressures, but exposed to high traction levels, the failure of the tensile armor connection due to disruption of the outer plastic layer has been appointed as the main failure mode to be investigated. The breakdown of protective layers allows the passage of corrosive solutions (gas and sea water) into the duct, accelerating the degradation process by the combination of factors associated with fatigue and corrosion. As a result, the verification of useful life of these risers is becoming increasingly important, justifying the development of reliable methods of inspection and high technologies that increase the estimated life of the components. In this study, the effects of the surface chemical modification of titanium dioxide (TiO2) nanoparticles and their addition into polyamide 11 (PA11) on the mechanical, dynamic-mechanical, and tribological properties of PA11/TiO2 nanocomposites were investigated, aiming the use in the outer plastic layer of offshore risers. The nanoparticles were incorporated by means of two different processes: by extrusion and by internal mixer Haake. The results led to the conclusion that the incorporation of titanium dioxide nanoparticles (TiO2) in a polyamide 11 (PA11) matrix has promising application potential in increasing the life cycle of the outer layer, especially with regard to increased the wear resistance. However, this conclusion is valid only if an appropriate dispersive and distributive mixing is obtained, since the differences between modified and non-modified composites are more strongly influenced by the dispersion of load than by the chemical compatibility between the PA 11 matrix and the modifier.